A wireless instrumented insole for monitoring plantar pressure during human locomotion - Mariana Alegria; Mariana Ballesteros; David Cruz-Ortiz (Sensing and Bio-Sensing Research)
This work proposes a wireless instrumented insole for monitoring plantar pressure (PP) during human locomotion. The insole is composed of two elements. The first is a mold manufactured with thermoplastic polyurethane using tridimensional printing techniques. The second one is a soft cover fabricated with a liquid polymer Ecoflex™ 00–30 from Smooth-On. The insole considers a microcontroller Arduino Nano and 24 force-sensing resistors located in ten anatomic regions of the foot with a sampling frequency of 70 Hz. The device sends the data through wireless communication based on a Bluetooth module to a graphical user interface in a computer where the data is received, displayed, and stored. A test was carried out with ten healthy volunteers (five men and five women) to validate the PP measured with the device. The data obtained were analyzed and compared with the literature, considering relevant characteristics in the PP analysis.